Maternal early pregnancy obesity and depressive symptoms during and after pregnancy. Issue 14 (17th January 2018) - Kumpulainen, Satu M.; Girchenko, Polina; Lahti-Pulkkinen, Marius; Reynolds, Rebecca M.; Tuovinen, Soile; Pesonen, Anu-Katriina; Heinonen, Kati; Kajantie, Eero; Villa, Pia M.; Hämäläinen, Esa; Laivuori, Hannele; Räikkönen, Katri
Abstract: Background: Previous studies have linked maternal obesity with depressive symptoms during and after pregnancy. It remains unknown whether obesity associates with consistently elevated depressive symptoms throughout pregnancy, predicts symptoms postpartum when accounting for antenatal symptoms, and if co-morbid hypertensive and diabetic disorders add to these associations. We addressed these questions in a sample of Finnish women whom we followed during and after pregnancy. Methods: Early pregnancy body mass index, derived from the Finnish Medical Birth Register and hospital records in 3234 PREDO study participants, was categorized into underweight (<18.5 kg/m 2 ), normal weight (18.5–24.99 kg/m 2 ), overweight (25–29.99 kg/m 2 ), and obese (⩾30 kg/m 2 ) groups. The women completed the Center for Epidemiological Studies Depression Scale biweekly during pregnancy, and at 2.4 (s.d. = 1.2) and/or 28.2 (s.d. = 4.2) weeks after pregnancy. Results: In comparison to normal weight women, overweight, and obese women reported higher levels of depressive symptoms and had higher odds of clinically significant depressive symptoms during (23% and 43%, respectively) and after pregnancy (22% and 36%, respectively). Underweight women had 68% higher odds of clinically significant depressive symptoms after pregnancy. Overweight and obesity also predicted higher depressive symptoms after pregnancy in women not reporting clinically relevant symptomatology during pregnancy. Hypertensive and diabetic disorders did not explain or add to these associations. Conclusions: Maternal early pregnancy overweight and obesity and depressive symptoms during and after pregnancy are associated. Mental health promotion should be included as an integral part of lifestyle interventions in early pregnancy obesity and extended to benefit also overweight and underweight women.